1980
DOI: 10.1152/ajpheart.1980.239.1.h14
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive regulation of wall shear stress to flow change in the canine carotid artery

Abstract: To study the adaptive response of the vascular wall to blood flow changes, an arteriovenous shunt was constructed between the common carotid artery and the external jugular vein in 12 dogs. Six to eight months postoperatively, the arterial internal radius (r) was determined by angiography and/or the use of pressure-volume relationship. The results showed that r increased with increased flow load (f) and vice versa. Wall shear rate (gamma) was calculated from gamma = 4f/(tau r3), assuming laminar flow. The valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
410
0
21

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(450 citation statements)
references
References 16 publications
19
410
0
21
Order By: Relevance
“…The remodeling of blood vessels in response to flow-overload obeys the constant WSS hypothesis (23,39). This principle implies that the volumetric flow rate is proportional to the cube of the vessel radius assuming a laminar, incompressible, Newtonian flow through a rigid cylindrical vessel (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remodeling of blood vessels in response to flow-overload obeys the constant WSS hypothesis (23,39). This principle implies that the volumetric flow rate is proportional to the cube of the vessel radius assuming a laminar, incompressible, Newtonian flow through a rigid cylindrical vessel (24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, changes in blood flow cause changes in fluid wall shear stress (WSS; the tractive frictional force exerted by flowing blood on the inner layer of the vessel wall) by eliciting a wide range of biochemical and physiological responses in experimental (46) and clinical studies (16,22). Studies have demonstrated that a sudden increase in blood flow initiates an enlargement of the arterial lumen that progresses for months as the WSS tends to a homeostatic or normal level (23,25). A gradual increase in blood flow has been reported by several groups to result in outward hypertrophic remodeling of resistance (4,41,44,45,47) and conductive arteries (25,36,39).…”
mentioning
confidence: 99%
“…Second, the endothelium in controlling lumen size regulates SS in a negative feedback control loop. 18 Therefore, cross-sectional SS increments (induced by wall thickening, Figure 4C) will induce positive vascular remodeling, 6 causing SS to decrease. However, almost any control loop will leave some residue of the initial disturbance.…”
Section: Local Effectsmentioning
confidence: 99%
“…His lecture was: "Blood vessels change their sizes (vascular diameters) in response to changes in the blood flow, and this vascular remodeling is an adaptive response aimed at keeping the shear stress on the vascular wall (a biomechanical force arising from flow ing blood) constant, enabling maximization of the efficiency of the vascular work from the viewpoint of consumed energy [1]. Since the vascular endothelium is exposed to shear stress, blood flow dependent remodeling of blood vessels probably arises when the vascular endothelium senses shear stress.…”
Section: Encounter With Biorheologymentioning
confidence: 99%